A Pragmatic Analysis of Politeness Strategies Applied in the Use of Humorous Phatic Utterances - Dedi Febrianto (English Education Department, 2019)
Abstract: As opposed to informational purposes, phatic utterances hold a bigger role in human communication that is to keep social relations among people. Though people hardly ever notice the importance of phatic utterances, these are the utterances that indispensable in their daily basis communication used to avoid the sense of impoliteness, especially when meeting people they are familiar with. In uttering phatic, people use a variety of ways including raising humor. The humourous phatic utterances are interesting to be analyzed in order to investigate the implementation of politeness strategies used along with the production of phatic utterances. To the researcher's best knowledge, the link between humorous phatic utterances and politeness strategies has not become the concern of previous researches. Therefore, this research was conducted to describe phatic utterances conveyed by the characters of a widely known situation comedy (sitcom) Friends and also to find out the politeness strategies applied when uttering the phatic utterances. The researcher used solidarity and deference of politeness strategies as proposed by Yule (1996) to analyze each phatic utterance found. The design of this research was descriptive qualitative. The data were documented from the sitcom episode 21-24. The data were analyzed by describing the context used and giving the explanation of each datum that was included in phatic utterances. After conducting the analysis, it is found that there are 37 phatic utterances used in the sitcom. Politeness strategies are always applied in any phatic utterances found and the most frequently used politeness strategy is solidarity strategy.